'I'm too busy to teach'. Tips for teaching when time is tight. Issue 1 (14th December 2021) - McLaughlin, Diarmuid; Mulholland, Melissa; McKenna, Dearbhla; Mallett, Peter; Lewis, Julie
Abstract : Prioritising teaching when clinical practice is hectic can be difficult. Often teaching is seen to be confined to formal structured events. This article aims to highlight the abundance of learning opportunities that arise outside of such formal teaching events in daily clinical practice. It first discusses the qualities and skills of a time-efficient, yet effective, teacher. Practical suggestions are then provided in order to maximise learning from important opportunities that occur daily from handovers, ward rounds, clinics to tea-trolley teaching aiming to give encouragement to all that valuable teaching is possible even when time is limited.